Study of the low energy charged particles emitted in the interaction of 6 BeV and 27 BeV protons with silver and bromine nuclei. - Crouch, Kendal R. (University of Ottawa (Canada), 1965)
A study has been made of the low-energy charged particles emitted from the interactions of 6 BeV and 27 BeV protons with silver and bromine nuclei in nuclear emulsions. The energy spectra of the protons and alpha particles are compared with the Weisskopf evaporation theory and with experimental results at other bombarding energies. The evaporation temperatures of the excited nuclei were determined for the emission of protons (including deuterons and tritons) and alpha particles, respectively, for the two primary proton energies of 6 BeV and 27 BeV. The two proton energy spectra are consistent with an evaporation temperature of 4 to 5 MeV and a potential barrier V° ∼ 3-4 MeV. For the alpha particle spectra, the parameters for the evaporation curves which give the best fit to the experimental distributions are a temperature, T, of the order of 10 to 12 MeV and a potential barrier V° very nearly equal to zero. These abnormally high temperatures (greater than the binding energy of a nucleon inside the nucleus) indicate the emission process cannot be entirely explained in terms of a normal mechanism of evaporation from a thermodynamic equilibrium state. Applying the value of T obtained from the proton energy spectra, with a value of V° - 7-8 MeV, gives a satisfactory fit of the theoretical curve to the experimental distribution for alpha energies less than 30 MeV. A study of the angular distributions of the emitted particles alpha shows that the emission is anisotropic, the distribution being peaked in the forward direction; this peaking is more pronounced at 6 BeV than at 27 BeV. In both cases, the forward peaking appears to be due exclusively to alpha particles of energy greater than 30 MeV. We may conclude, therefore, that these higher-energy particles are probably associated with secondary interactions provoked by the cascade, rather than with the pure evaporation process. In an attempt to understand the processes of interaction of 6 BeV protons with heavy nuclei, the angular distributions of the black tracks have been studied for stars previously analyzed in terms of the charged pi-meson distribution. The results are discussed for the cases when the incident proton collides: (a) with a single nucleon in the target nucleus, and (b) with 3 to 5 target nucleons. The results indicate that the interactions with a single target nucleon occur at the periphery of the nucleus, the two nucleons then leaving the nucleus without initiating a cascade. The star size and the average excitation energy are found to be smaller for the single nucleon interactions than in the case of the (3-4-5) target nucleon interactions and the probability of fragment emission appears to be greater.
Keywords: Physics, Nuclear.